SINTESIS DAN KARAKTERISASI β-TRICALCIUM PHOSPHATE BERBASIS CANGKANG KERANG RANGA PADA VARIASI SUHU SINTERING - N. Selvia (Jurnal Biofisika, 2012)
Many cases of bone loss triggered growing research of bone biomaterial. Biomaterials are widely used for bone substitution is β-tricalcium phosphate (β-TCP). In this research was done the synthesis of β-TCP based on rangga shells. The use of natural materials (shells) can improve the bioactive properties and biocompatibility in the process of bone healing. Rangga shells obtained from the Riau Islands. Synthesis of β-TCP performed by reacting calcium from rangga shell and H3PO4 with precipitation method at a temperature of 80oC with variations sintering temperature to 800oC, 900oC, 1000oC, 1100oC, 1200oC, and 1300oC. To determine the phase formed in the samples analyzed using X-ray difraction (XRD). XRD pattern shows the presence of peaks belongs to β-TCP, hydroxyapatite (HA), carbonate apatite tipe-A (CAA), and oktacalcium phosphate (OCP). β-TCP optimum form on the β-TCP samples sintering temperature 1200oC holding time 7 hours with the percentage of β-TCP produces by 81,98%. The formation of β-TCP was also stregthened by the results of Fourier transform infrared characterization (FTIR) is characterized by the presence of phosphate (PO43-) and hydroxyl (OH-). Micrograph of scanning electron microscopy (SEM) on sample of β-TCP optimum β-TCP showed in the form of chunks that are composed into a coarse aggregate. β-TCP optimum sample has an average particle size of 693,65 nm were measured using the PSA.